Study of Etiological Pattern of Acute Meningo-Encephalitis Syndrome - Uddin, Mohammad Najim; Uddin Hassan, Md Mahtab (Bangladesh Journal of Neuroscience, 2018)
Background: Acute meningo-encephalitis syndrome is a medical emergency which claim urgent management. So the objectives of the present study was to find out aetiological factors and differentiating parameter between different types acute meningoencephalitis syndrome with minimum investigation. Methods: This hospital based observational study was carried out in medicine units of Chittagong Medical College. Fifty cases were studied who present with acute onset fever with central nervous system dysfunction. Results: In this study it reveals that hospital rate of bacterial meningitis was 26%, viral encephalitis was 34% and severe malaria was 26% among the patient with acute meningo-encephalitis syndrome. It shows that mean age (years) in viral encephalitis was 33.71, bacterial meningitis was 34.15 & in severe malaria was 27.92. It reveals that all patients of this series presented with acute onset fever (n=50,100%), maximum patients present with sign of meningeal irritation (n=44, 88%) & altered mental state (n=41,82%). Few patients was present with new onset seizure (n=11,22%) & neurologic deficit (n=1,2%). In Bacterial meningitis most patient was with low CSF glucose (n=10, 76.9%). In viral meningitis there were normal CSF glucose level (n=17,100%). High protein content in bacterial (n=13,100%) & Viral (n=15,88.2%) was found. It shows differential count of CSF WBC in different type of meningitis where in Bacterial meningitis it is neutrophils & in other type of meningitis it is the lymphocyte. Conclusion: CSF findings are hallmark of diagnosing various type of meningitis. CSF glucose and protein content found in this study significantly correlate with different etiology (p value = 0.000). Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 45-51